ANALISIS PENCAHAYAAN, PENGHAWAAN, DAN AKUSTIK DI APARTEMEN (THE SRINGLAKE BEKASI) - Ibnu Fatdil Haryoso; Widiyanti (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2022)
Residential buildings that are separated horizontally and vertically so that housing is available, THE SPRINGLAKE BEKASI is located in the SUMMARECON BEKASI area, JL. BULEVAR AHMAD YANI, KELURAHAN MARGAMULYA, KECAMATAN BEKASI UTARA, KOTA BEKASI. The Springlake is part of the Summarecon Bekasi area, located on the basella floor 11th floor unit 19. Data collection using digital lux meters for natural and artificial lighting data, Sling Psychrometer for ventilation data, and sound level meter for acoustics. Quantitative approach because the results are numbers compared to the standard sni. The value of natural light in unit 19 is 258 lux while the corridor on the 11th floor is 367.5 lux, this value is above the standard 120-250 lux. Artificial lighting in unit 19 is 26 lux while the corridor on the 11th floor is 50.5 lux, this value is below the standard 120-250 lux. ventilation in unit 19 is 27oC in accordance with the SNI standard, namely 20.5oc - 27.1oc. in the 11th floor corridor is 29oc the value is above the Sni standard which is 20.5oc - 27.1oc, the acoustic value of unit 19 is 62.1 db while the 11th floor corridor is 59.5 db the value is above the Sni standard of 45 db - 55 db.